Assessment of the antiproliferative activity on murine melanoma cells of extracts from elicited cell suspensions of strawberry, strawberry tree, blackberry and red raspberry. (1st November 2016) - Forni, C.; Frattarelli, A.; Lentini, A.; Beninati, S.; Lucioli, S.; Caboni, E.
Abstract : The antiproliferative activity of extracts from cell suspensions of strawberry ( Fragaria x ananassa Duch.), blackberry ( Rubus fruticosus L.), red raspberry ( Rubus idaeus L.) and strawberry-tree ( Arbutus unedo L.) on murine B16-F10 melanoma cells was investigated. To enhance the synthesis of the bioactive compounds, various elicitors, i.e. temperature (cold and cold/warm cycle), light (blue and red) and increased nitrogen concentration, were also applied to the cell cultures to evaluate the effects on their antiproliferative activity. The extracts from all the species reduced murine melanoma cell proliferation (between 30% and 38% relative to the control) and an improvement of antiproliferative activity on murine melanoma cells, relative to the un-elicited berry suspensions, was shown by the extracts from strawberry and strawberry-tree cells treated with red and blue light.